2003
DOI: 10.1590/s0103-64402003000100004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-pathological parameters in squamous cell carcinoma of the tongue

Abstract: The correlation between TNM classification and histological scores of malignancy, and the correlation of these parameters with the prognosis was evaluated in 16 cases of squamous cell carcinoma of the tongue. The cases were selected from the files of "Dr. Luiz Antônio" Cancer Hospital, Natal, RN, Brazil. After analysis of the patients' records, the data concerning TNM classification and prognosis (in a 5-year-follow-up) were obtained. All cases were classified according to the histological malignancy grading s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 14 publications
1
40
1
10
Order By: Relevance
“…There are strong clinical evidences that OSCC has a worse prognosis when present in the tongue. Moreover, it usually shows a more infiltrative invasion and, therefore, predispose to the formation of metastasis 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are strong clinical evidences that OSCC has a worse prognosis when present in the tongue. Moreover, it usually shows a more infiltrative invasion and, therefore, predispose to the formation of metastasis 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Tongue, buccal mucosa, alveolus, palate, lip and floor of the mouth are in an ascending order of occurrence of OSCC in the oral cavity. [6,7] The worldwide epidemiological studies done on tongue squamous cell carcinoma. [ Table 4] Mehrota et al [8] found 42.6 %, Agarwal et al [9]found 16.2% and Shenoi et al [7] found 18.3% cases involving tongue ,while Selvamani et al [10] found 54 cases (14.1%) involving tongue OSCC in his study.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of advancements in the field of cancer diagnosis and availability of latest treatments, survival rates are not satisfactory. This is mainly due to unpredictable behavior of these lesions [2].Mast cells are connective tissue cells that are scattered along the capillaries, characterized by having abundant basophilic granules. Paul Ehrlich in 1878 first described mast cells as "mast zellen" meaning feeding cells in Greek.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, accumulation of mast cells appears to potentiate vessel growth [3,4].Studies have shown that OSCC is associated with chronic inflammation, immune reaction and angiogenesis with the progression of dysplastic changes. Hence, there is a need to assess the role of mast cells in OSCC [1][2][3].Our study was carried out to compare mast cell density in normal mucosa and squamous cell carcinoma and to assess the role of mast cells in oral squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%